2014
DOI: 10.1016/j.actbio.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Peri- and intra-implant bone response to microporous Ti coatings with surface modification

Abstract: Bone growth on and into implants exhibiting substantial surface porosity is a promising strategy in order to improve the long-term stable fixation of bone implants. However, the reliability in clinical applications remains a point of discussion. Most attention has been dedicated to the role of macroporosity, leading to the general consensus of a minimal pore size of 50-100 μm in order to allow bone ingrowth. In this in vivo study, we assessed the feasibility of early bone ingrowth into a predominantly micropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 58 publications
3
46
0
Order By: Relevance
“…The remodeling process was accompanied by the appearance of osteoclasts. A higher number of osteoclasts at the implant interface at 3 and 6 weeks and a clear reduction of osteoclasts at 12 weeks after implantation was also found in other studies (Braem et al, 2014;Reigstad et al, 2007). In the present work, a higher number of osteoclasts was observed at the implant interface in case of the CaP coated samples (Figure 7) that could also have had a stimulatory effect on bone remodeling via the intimate crosstalk between osteoclasts and osteoblasts (Kular, Tickner, Chim, & Xu, 2012 (Reigstad et al, 2007).…”
Section: Histomorphometric Analysissupporting
confidence: 89%
“…The remodeling process was accompanied by the appearance of osteoclasts. A higher number of osteoclasts at the implant interface at 3 and 6 weeks and a clear reduction of osteoclasts at 12 weeks after implantation was also found in other studies (Braem et al, 2014;Reigstad et al, 2007). In the present work, a higher number of osteoclasts was observed at the implant interface in case of the CaP coated samples (Figure 7) that could also have had a stimulatory effect on bone remodeling via the intimate crosstalk between osteoclasts and osteoblasts (Kular, Tickner, Chim, & Xu, 2012 (Reigstad et al, 2007).…”
Section: Histomorphometric Analysissupporting
confidence: 89%
“…This particular surface texture, EBM-produced cp-Ti and Ti-alloy scaffolds, has also been shown to promote cell attachment, proliferation and differentiation [9,27]. Previous studies with porous titanium have shown that surface irregularities with similar dimensions permit bone ingrowth [28,29]. This was also observed for the present surface texture creating firm mechanical interlocking, resulting in shear forces combined with other forces acting at the interface [30,31].…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, the pore structure is fully interconnected as the open porosity equals the total porosity. The pore window size distribution is relatively small around 1-2 m, but is still relevant for implant applications as we have recently shown that bone ingrowth for pore window sizes between 1 and 10 m is still possible [48].…”
Section: Discussionmentioning
confidence: 99%